Invasion of Alien Angiosperm Species in Wetlands of Shaheed Chandra Shekhar Azad Bird Sanctuary (SCSABS), Uttar Pradesh, India - Prajapati, Vinay Kumar; Singh, M.P.V. Vikram (Indian Forester, 2025)
The expansion of invasive alien species in wetlands leads to a reduction in native plant diversity. Invasive weeds are also responsible for the shrinking of water bodies, and becoming a severe environmental problem. In this context, plant diversity of wetlands in the Shaheed Chandra Shekhar Azad Bird Sanctuary (SCSABS), Unnao, Uttar Pradesh, was surveyed. Eighty five species of higher plants have been listed of which 71 were dicots followed by 14 monocots, belongs to 39 different families. Amarantheaceae is the dominant family with 7 species followed by Asteraceae, Fabaceae, Poaceae (6), Mimosaceae (5), Malvaceae (4), Convolvulaceae, Cyperaceae, Euphorbiaceae, Onagraceae, Solanaceae (3), Acanthaceae, Asclepidiaceae, Moraceae, Myrtaceae, Oxilidaceae, Pontederiaceae, Scrophularaceae, Tileaceae (2) and rest twenty families represented by only one species. The presence of Eichhornia crassipes, Typha angustata, Prosopis juliflora and Ipomoea carnea are considered as one of the most serious threat to the Shaheed Chandra Shekhar Azad Bird Sanctuary (SCSABS) wetland. A better planning in the form of early identification and reporting of identification and spread of noxious weeds is needed for their control.